IMPLEMENTASI DESAIN READY TO WEAR ANAK PEREMPUAN DENGAN TEKNIK BATIK TULIS - Monica Amelia Suhendar (Universitas Ciputra Surabaya, 2019)
“IMPLEMENTATION DESIGN READY TO WEAR FOR DAUGHTER USING BATIK TECHNIQUE ” This design in order to cultivate batik culture in children from an early age on the ready-to-wear design collection for girls with innovation on animal pattern using batik for Kiddotik brand. The target market of Kiddotik is woman aged 25-35 years old who have girls aged 2-6 years old. It will be designed a collection with the final product that is applied technique of batik with animal pattern based on the result of through research interview expert and potential customer, observation, literature study.